BCR-ABL1 e6a2 transcript in chronic myeloid leukemia: biological features and molecular monitoring by droplet digital PCR. - Zagaria, Antonella; Anelli, Luisa; Coccaro, Nicoletta; Tota, Giuseppina; Casieri, Paola; Cellamare, Angelo; Impera, Luciana; Brunetti, Claudia; Minervini, Angela; Minervini, Crescenzio Francesco; Delia, Mario; Cumbo, Cosimo; et al. (Virchows Archiv: European Journal of Pathology, 2015)
The BCR-ABL1 fusion on the Philadelphia (Ph) chromosome is a hallmark of chronic myeloid leukemia (CML). More than 95 % of BCR-ABL1 transcripts in CML are either e13a2 or e14a2 (major breakpoint cluster region or M-bcr), whereas rare BCR-ABL1 transcripts are occasionally observed, accounting for less than 1 % of CML cases. Among these, a very rare fusion transcript joining the first 6 exons of BCR to exon 2 of ABL1 (e6a2) has been reported in various hematological malignancies characterized by an aggressive clinical course. We report a new case of blast crisis (BC) CML with an e6a2 fusion transcript characterized by many eosinophil precursors with abnormal granules. Moreover, fluorescence in situ hybridization analysis revealed genomic deletions of 1.3 megabases and 342 kilobases on der(9) of chromosome 9 and 22 sequences, respectively. The fusion transcript was quantified at diagnosis and during follow-up using digital droplet polymerase chain reaction (ddPCR) technology. The patient was treated with Dasatinib (140 mg/day), resulting in a 3-log reduction of the e6a2 transcript molecular burden from the third month after treatment. In this twentieth e6a2 case, characterized by marked eosinophilic dysplasia, deletions on der(9), and responsive to tyrosine kinase inhibitors therapy, we demonstrate that for molecular response monitoring of rare fusion transcripts associated with CML, ddPCR is a very useful technology.